2013
DOI: 10.1017/s0376892913000507
|View full text |Cite
|
Sign up to set email alerts
|

Cognisance, participation and protected areas in the Yucatan Peninsula

Abstract: SUMMARYLocal people's involvement in the management of conservation initiatives is central to ongoing debates on the relative merits of distinct biodiversity conservation models. Since different governance models provide distinct opportunities for local people to participate in the management of protected areas, their knowledge of these governance models and motivation to collaborate will vary. This paper analyses cognisance and participation in (1) government-imposed biosphere reserves and (2) community conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
0
7
0
2
Order By: Relevance
“…Despite this declaration of intent, it should be noted that opinions, modifications or adaptations that arise from the participation process are not binding to the management body, as final decisions are made unilaterally by CONANP. As a consequence, and despite the attempts to bring people in PA, this model continues to be considered an exclusionary conservation model (Berkes 2007;Paulson et al 2012;Ruiz-Mallén et al 2014).…”
Section: Protected Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this declaration of intent, it should be noted that opinions, modifications or adaptations that arise from the participation process are not binding to the management body, as final decisions are made unilaterally by CONANP. As a consequence, and despite the attempts to bring people in PA, this model continues to be considered an exclusionary conservation model (Berkes 2007;Paulson et al 2012;Ruiz-Mallén et al 2014).…”
Section: Protected Areasmentioning
confidence: 99%
“…Many programs ignore the fact that diverse perceptions and interests may exist within one group in relation to the areas dedicated to conservation (Haenn 1999;Rodríguez-Izquierdo et al 2010). This lack of consideration can act as a disincentive to participation, above all among those who appear to be excluded for reasons of gender, age, or other social characteristics (Agarwal 2001;Merino 2013;Ruiz-Mallén et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from Nicaragua, Mexico, Ethiopia, Botswana and Kenya, among others, has shown that top-down conservation interventions can also lead to people's displacement from their original territories (Adams and Hutton, 2007;Kaimowitz et al, 2003;Ruiz-Mallé n et al, 2014). Forced migration in the interest of conservation increases people's vulnerability and can also result in people's dispossession from their native land (Dowie, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The action situations were different instances of local collective action in support of natural resource management and rural livelihoods: (1) collective control of land 26 use as between shrimp farming and cropping; (2) collective water resource management; (3) a social forestry initiative; and (4) collective response to cyclone-related disasters. The first two cases were chosen as being largely community-initiated while the last two were initiated through planned interventions (the Social Forestry Program and the Cyclone Preparedness Program, respectively) to enable some comparison between predominantly local or external drivers of collective action.…”
Section: Research Strategymentioning
confidence: 99%
“…Research shows that social forestry needs effective government support in various forms, including strengthening local links with external institutions, establishing the legal basis of community forestry, providing technical assistance and training in group management, and providing funding and infrastructure (Hodgdon 2010;Pulhin et al 2010;Ruiz-Mallén et al 2014). At the same time, studies have found that, rather than giving power and resources to local people, government bureaucracies pay lip-service to community forestry due to pressure from development agencies (Hajjar et al 2011;Hodgdon 2010;Islam and Sato 2010;Jashimuddin and Inoue 2012;Muhammed et al 2005Muhammed et al , 2008.…”
Section: Lack Of Effective State Supportmentioning
confidence: 99%